Clinical study of prolene hernia system in inguinal hernia repair - Obaid, Syed; Quazi, Sohail (International Surgery Journal, 2017)
Background: Lichtenstein was first to coin the term "tension-free hernioplasty" in his book "Hernia repair without disability". All direct, indirect and recurrent adult hernias can be repaired by this procedure. The objective of this study was to determine the feasibility of using the prolene (polypropylene) hernia system for open tension-free repair on inguinal hernias. Methods: During period of 2 years, 42 patients were subjected to prolene hernia. Of these 42 patients, 3 patients underwent bilateral repair. Thus, in all 45 inguinal hernias were repaired. The median age of patients in our study was 57 years. In our study majority hernias were indirect inguinal hernias (47.61%). Nineteen (45.23%) hernias were of direct type while 2 (4.76%) pantaloon and 1 recurrent inguinal hernias. Out of the 42 patients, 16 were operated under local anesthesia while 17 patients operated under spinal anesthesia. Maximum hernias were Gilbert’s type III hernias. Results: The duration of surgery averaged 35 min (range 20-90 min). There were no postoperative deaths. Two out of 42 patients developed local infection at wound site. Wound seroma was found in 3 patients but subsided by giving antibiotics and patients were discharged as per routine protocol. 2 patients (4.76%) developed mild pain in testicular region which subsided with non-steroidal anti-inflammatory drugs. One patient (2.38%) in our series had pain in operative region that lasted for more than one month, only non-steroidal analgesics sufficed to deal with this problem and no patient complained of pain after 2 months of surgery. No patient in our series developed late infection or testicular atrophy. No recurrence was noted during the period of follow-up. This was consistent with the result of other series performed worldwide. Most of the patients in our study (18 patients i.e. 42.87%) were discharged on 3rd postoperative day. One patient had mild neuralgia up to maximum of 2 months in the follow up period which subsided with analgesics. No recurrence was seen in the follow up period. Conclusions: The prolene hernia system is a novel approach in the management of inguinal hernias, with encouraging initial results. Its long-term efficacy needs to be studied with larger, prospective double-blind randomized trials, with longer follow-up.